1994
DOI: 10.1002/ar.1092400304
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and immunocytochemical study on normal human palmar aponeuroses

Abstract: Independently of the age, normal palmar aponeurotic cells show peculiar morphological features and peculiar cell-matrix interactions, very likely mediated by hyaluronan. These findings indicate that normal aponeurotic cells cannot be regarded as typical tenocytes and suggest the need for a better definition of their phenotype in order to understand their behaviour in pathological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The magnitude of this force deficit is a function of strain and the work done to stretch the contractile component (CC) of muscle (8). The aponeurosis (intramuscular tendon) and the tendon, composed chiefly of type I and III collagen (12,22,27), form the series elastic component (SEC) of muscle (23). A positive correlation exists between the collagen content and stiffness of a muscle (16,19,48).…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this force deficit is a function of strain and the work done to stretch the contractile component (CC) of muscle (8). The aponeurosis (intramuscular tendon) and the tendon, composed chiefly of type I and III collagen (12,22,27), form the series elastic component (SEC) of muscle (23). A positive correlation exists between the collagen content and stiffness of a muscle (16,19,48).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, based on the evidence of their study on bioptic samples from normal subjects of different ages by means of optical and electron microscopic analyses and by immunocytochemistry (12). Also, Contri et al indicated that normal aponeurotic cells cannot be regarded as typical tenocytes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent histological studies suggest that the plantar fascia is histologically distinct from tendons and ligaments. 28,29 Plantar fasciitis involves predominantly the proximal insertion of the aponeurosis (enthesis) 30,31 The enthesis consist of 4 zones: dense fi brous collagenous tissue, uncalcifi ed fi rbrocartilage, calcifi ed fi brocartilage and bone. 32,33 The prevalence of fi brocartilage insertions in areas which experience stress in more than one degree of freedom [34][35][36] suggests that entheses are specifi cally adapted to shearing and bending forces.…”
Section: Discussionmentioning
confidence: 99%